POST THERAPEUTIC NEUROLOGICAL MANIFESTATION OF TRYPANOSOMIASIS IN A DOG - FATAL CASE REPORT - C. Jayanthy,; S. Abinaya,; G. R. Baranidharan,; A. Gopalakrishnan,; Rajat Sagare,; K. Jeyaraja,; Subapriya,; C. M. Madhumitha,; K. Jothimeena,; Ashi R Krishna,; R. Sokkalingam, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A five-year-old intact male non-descript dog was referred to the Madras Veterinary College Teaching Hospital with a history of blindness, persistent fever, inappetence, lethargy and corneal opacity for a week. Clinical examination revealed pale mucous membrane, pyrexia, and enlarged superficial lymph nodes and ophthalmic examination confirmed bilateral corneal opacity (5/5) and related vision loss. Hemato-biochemical profile revealed anemia, thrombocytopenia, hypoproteinemia, hypoalbuminemia and elevated creatinine levels. The wet film examination was positive for Trypanosoma evansi (+++) and following which the animal was treated with Diminazene aceturate @ 3.5 mg/kg deep IM, tab. Prednisolone @0.5 mg/kg, oral hematinics and evaluated after 2 weeks. Corneal opacity cleared After 14 days of treatment; haemato-biochemical parameters were back to normal range, and after one week of clinical recovery, the dog showed neurological signs. Abdominal ultrasonography revealed mild splenomegaly, ocular ultrasonography revealed normal ocular structure. CSF was positive by PCR for Trypanosoma evansi upon which the animal succumbed to death.